Arctic Oil and Gas 2007. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2007)
"The objective of the 2007 'Assessment of Oil and Gas Activities in the Arctic' is to present a holistic assessment of the environmental, social and economic, and human health impacts of current oil and gas activities in the Arctic, and to evaluate the likely course of development of Arctic oil and gas activities and their potential impacts in the near future. The assessment updates information contained in the AMAP 1997/98 assessment reports, including several aspects not covered in the earlier assessments regarding impacts of oil and gas activities in the Arctic. The assessment also includes recommendations to the Ministers for their consideration. This 'State of the Arctic Environment Report' is intended to be readable and readily comprehensible, and does not contain extensive background data or references to the scientific literature. The complete scientific documentation, including sources for all figures reproduced in this report, is contained in a related report, 'Assessment 2007: Oil and Gas Activities in the Arctic - Effects and Potential Effects', which is fully references. For readers interested in the scientific background to the information presented in this report, we recommend that you refer to the scientific report." Norway, United States of America, Nordic Council of Ministers.